2017
DOI: 10.1177/0003489417728089
|View full text |Cite
|
Sign up to set email alerts
|

Venous Complications in One Versus Two Vein Anastomoses in Head and Neck Free Flaps

Abstract: Two-vein anastomoses do not appear to reduce rates of flap failure or postoperative venous thrombosis but are associated with a lower number of reexplorations in the operating room even after accounting for differences in flap types and surgeons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…18 Conversely, Khaja et al proved that two vein anastomoses in head and neck free flap did not reduce flap failure rate or postoperative venous thrombosis. 19 In this study, the number of recipient veins did not have any impact on the speech outcome after tongue reconstruction. Further large-scale studies are warranted to verify the correlation between the number of vein anastomosis and the functional outcome of the free flap in head and neck reconstruction.…”
Section: Discussionmentioning
confidence: 51%
“…18 Conversely, Khaja et al proved that two vein anastomoses in head and neck free flap did not reduce flap failure rate or postoperative venous thrombosis. 19 In this study, the number of recipient veins did not have any impact on the speech outcome after tongue reconstruction. Further large-scale studies are warranted to verify the correlation between the number of vein anastomosis and the functional outcome of the free flap in head and neck reconstruction.…”
Section: Discussionmentioning
confidence: 51%
“…On 854 patients, it was demonstrated that factors, such as age, smoking, and prior irradiation, in particular, do not affect flap survival [20]. Because venous thrombosis is the most common cause of vascular complications, many surgeons recommend anastomosing two veins [21][22][23]. Interestingly, in regression analysis, we could not find any advantage of dual or triple venous anastomosis compared to a single-vein anastomosis (P = 0.904).…”
Section: Discussionmentioning
confidence: 82%
“…Hence, opined that execution of two venous anastomoses has significant effect on reducing the vascular compromise and free flap failure rate in head and neck reconstruction. One more study done by Khaja et al (2017) compared 229 patients with one vein anastomosis and 71 patients of two vein anastomosis, concluded that two vein anastomoses did not reduce the flap failure rate or the post‐operative venous thrombosis. In lower limb majority of the studies found that number of vein anastomoses did not influence the flap success or failure rate.…”
Section: Discussionmentioning
confidence: 99%